Water Quality Assessment of Smaquli Dam- Erbil for Drinking, Irrigation and Fish Farming - Glena Ali Mahmood; Farhad Hassan Aziz (مجلة بغداد للعلوم, 2024)
This study was devoted to characterizing the water quality of Smaquli Dam, based on the calculation method of using the Water Quality Index (WQI) for drinking, irrigation and fish farming purposes. Water samples were collected from eight sites monthly from September 2021 to June 2022. The water quality index (WQI) was determined for drinking purposes based on the most important fifteen physical and chemical parameters, including; pH, electrical conductivity, turbidity, dissolved oxygen, biochemical oxygen demand, total alkalinity, total hardness, calcium and magnesium ions, sodium, potassium, chloride, nitrite, nitrate and sulphate. The relative weight of each parameter varied from 1 to 5 based on the most critical important parameter essential for aquatic life, domestic use and household. The results indicated that the water of the Smaquli Dam, with its inlet and outlet, is suitable for drinking after traditional treatment (DWQI) of all sites ranging from (68.11 to 83.93). However, for the irrigation water quality index (IWQI), studied samples were analyzed for EC, sodium adsorption ratio (SAR), sodium (Na+1), chloride (Cl-1) and bicarbonate (HCO3-1) contents. The results of (IWQI) ranged from (68.84 to 70.20), which means that the water samples fall within the class of low (LR) and moderate restriction category (MR) for irrigation purposes. Finally, six parameters including: pH, turbidity, TDS, DO, Total Hardness and Nitrate were determined to evaluate Smaquli dam water quality for fish farming based on standard limits for each parameter. The results for all parameters of all locations were within the permissible standard limit for fish farming except total hardness parameter.